ENERGY-DEPENDENT FRACTIONAL STURM-LIOUVILLE IMPULSIVE PROBLEM - Metin Turk, Funda; Bas, Erdal (Vinca Inst Nuclear Sci, 2019)
In study, we show the existence and integral representation of solution for energy-dependent fractional Sturm-Liouville impulsive problem of order with alpha is an element of (1,2] impulsive and boundary conditions. An existence theorem is proved for energy-dependent fractional Sturm-Liouville impulsive problem by using Schaefer fixed point theorem. Furthermore, in the last part of the article, an application is given for the problem and visual results are shown by figures.
Keywords: Sturm-Liouville problem; energy dependent; fractional; impulsive condition; Caputo derivative